Development of a Framework of Adaptable Guidelines and Incorporating Medical Nutrition Education into Medical School Curriculum. - Phelan, Grace. (Tufts University. Tisch Library., 2018)
This posters details the development of a framework if adaptable guidelines for incorporating medical nutrition education into medical school curriculums, particularly in Malawi.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy